Development of a grit scale for public school SPED teachers - Santos, Khristine Angelica B. (Animo Repository, 2023)
The study adopted the sequential exploratory mixed-method design to explore the grit of public school SPED teachers and to develop a grit rating scale with sound psychometric properties. The findings of the study revealed that gritty public school SPED teachers employ cognitive traits (i.e., strategic mindset) and non-cognitive traits (i.e., positive feelings and persistence) when working on a long-term goal. Furthermore, the study developed a 12-item PST Grit Scale that measured grit according to the cognitive and non-cognitive traits. Its initial psychometric properties showed that it is a valid and reliable tool that can measure the grit of public school SPED teachers. The study suggests that the PST Grit Scale can be used by public school SPED administrators and SPED teachers to measure grit accordingly and to devise programs that can foster teachers’ grit further. It is also suggested for future studies to examine and to compare its psychometric properties with other teacher grit scales, to expand its generalizability by replicating the study to more participants, and to investigate its ability to measure grit over a long period of time. Keywords: grit scale, public school SPED teachers, mixed method